Drivers of the Abundance of Tridacna spp. Giant Clams in the Red Sea - Rossbach, Susann; Anton, Andrea; Duarte, Carlos M. (Frontiers in Marine Science, 2021)
Giant clams (Subfamily Tridacninae), are important members of Indo-Pacific coral reefs, playing multiple roles in the framework of these communities. Although they are prominent species in Red Sea reefs, data on their distribution and densities in the region are scarce. The present study provides the first large-scale survey of Red Sea Tridacna spp. densities, where we examined a large proportion of the Saudi Arabian Red Sea coast (1,300 km; from 18˚ to 29˚N). Overall, Tridacninae were found at densities of 0.19 ± 0.43 individuals m-2 (± SD). Out of the total 4,002 observed clams, the majority (89 %) were Tridacna maxima, with 0.17 ± 0.37 individuals m-2, while only 11 % were Tridacna squamosa clams with 0.02 ± 0.07 individuals m-2. We also report on a few (total 6) Tridacna squamosina specimens, found at a single reef. We identified different geographical parameters (i.e., latitude and distance to shore) and local environmental factors (i.e. depth and reef zone) as the main drivers for local Tridacna spp. densities. Our results show that the drivers influencing the densities of Red Sea giant clams are complex due to their co-occurrence and that this complexity might explain the high variation in Tridacninae abundances across the Indo-Pacific, but also within a given reef. We also estimate that giant clam calcification likely contributes to an average of 0.7 %, but potentially up to 9 %, of the overall mean calcium carbonate budget of Red Sea coral reef communities.